Risk and treatment of symptomatic epidural hematoma after anterior cervical spine surgery: A retrospective clinical study - Liao, Yehui; Tian, Yang; Ye, Rupei; Tang, Chao; Tang, Qiang; Ma, Fei; Yang, Sheng; He, Hongchun; Zhong, Dejun (Medicine (Baltimore), 2020)
Symptomatic epidural hematoma (SEH) after anterior cervical spine surgery is very rare, but it has disastrous consequences for the patients. Timely diagnosis and evaluation can effectively reduce the sequelae of neurological deficit in SEH. The purpose of this study was to retrospectively analyze a subset of clinical data of SEH after anterior cervical spine surgery, and to investigate the risk factors and treatment experience of this serious complication.Neurological deterioration after anterior cervical spine surgery was detected in six patients. Epidural hematoma was confirmed by emergency cervical magnetic resonance imaging (MRI). The patients included five males and one female, with an average age of 56.7 ± 13.1 years (range 42-76 years). Three patients had a history of drinking and/or smoking. All of the patients were treated with nonsteroidal anti-inflammatory drugs (NSAIDs) preoperatively, but without anticoagulant drugs or pre-spinal surgery. The coagulation function was normal in all patients. Except for one patient, who had lower blood pressure (BP) during the operation and higher BP after the operation, the other patients had a normal level of BP during the pre-, intra-, and post-operation periods. The average time was 9.9 ± 6.7 hours (range, 2-19 hours) from the postoperative period to the initial neurological deficit and 6.3 ± 6.0 hours (range, 1.8-16.7 hours) from the initial deterioration to evacuation. Five patients underwent emergency evacuation, and one patient underwent conservative treatment. Four patients who underwent evacuation and one patient who received conservative treatment achieved neurological function recovery with an American Spinal Injury Association (ASIA) grade 2.4 ± 0.9 (range, 2-4 score) score at the last follow-up. One patient with confirmed arterial epidural hemorrhage during the evaluation showed no neurological function recovery at the last follow-up.Wide exposure of the epidural space and BP level during the perioperative period play an important role in the formation of SEH after anterior cervical spine surgery. Arterial epidural hematoma has serious consequences; therefore, early diagnosis and evaluation play an important role in the recovery from paralysis.